2001
DOI: 10.1046/j.1365-2265.2001.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo‐controlled trial of testosterone replacement in men with mild Leydig cell insufficiency following cytotoxic chemotherapy

Abstract: These results suggest that testosterone therapy in young men with raised LH levels and low/normal testosterone levels does not result in significant changes in BMD, body composition, lipids or quality of life, apart from a reduction in physical fatigue and a small reduction in LDL cholesterol. This implies that mild hypogonadism defined on this basis is not of clinical importance in the majority of men, and that androgen replacement cannot be recommended for routine use in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…The frequently prescribed 5α-reductase inhibitors for prostate enlargement can induce mild hypogonadal symptoms [Thompson et al 2003]. Many cancer treatments, such as alkylating agents, can significantly harm Leydig-cell function and spermatogenesis [Howell et al 2001]. Systemic glucocorticoids have direct inhibitory effects on all levels of the HPG axis, which can persist up to 12 months after cessation of therapy [Morrison et al 1994].…”
Section: Etiologies Of Hypogonadism In Aging Menmentioning
confidence: 99%
“…The frequently prescribed 5α-reductase inhibitors for prostate enlargement can induce mild hypogonadal symptoms [Thompson et al 2003]. Many cancer treatments, such as alkylating agents, can significantly harm Leydig-cell function and spermatogenesis [Howell et al 2001]. Systemic glucocorticoids have direct inhibitory effects on all levels of the HPG axis, which can persist up to 12 months after cessation of therapy [Morrison et al 1994].…”
Section: Etiologies Of Hypogonadism In Aging Menmentioning
confidence: 99%
“…[24][25][26] Similarly, merely replacing testosterone does not restore sexual function and satisfaction among men with abnormal hormonal profiles after bone marrow transplantation. 27 Sexual rehabilitation after cancer in women also cannot be reduced to a simple paradigm of hormonal replacement or a mechanical device. Despite promising results with using testosterone patches to treat low desire, 20 female cancer survivors have to consider their risk for breast cancer that may be potentiated by such therapy.…”
Section: Sexual Rehabilitation After Cancer Treatmentmentioning
confidence: 99%
“…The one study in younger adults examined a group of men with mild hypogonadism following treatment with gonadotoxic chemotherapy for cancer [55]. This study by our group differed from previous reports in that the definition of mild testosterone deficiency was based on both the luteinizing hormone (LH) level and the testosterone level, on the assumption that minor reductions in testosterone production would result in reduced hypothalamicpituitary negative feedback and therefore a rise in LH levels.…”
Section: Who To Treatmentioning
confidence: 46%
“…We demonstrated significantly lower femoral neck BMD, subtle changes in body composition and some reductions in sexual function in the study cohort compared with a control group of men who had undergone the same treatment for the same malignancies but had entirely normal LH and testosterone levels. However, testosterone replacement in these men did not result in any significant improvement in BMD, body composition, energy levels, mood or sexual function, and we concluded that androgen replacement could not be recommended for men with the mild biochemical abnormalities observed in this cohort [55]. Thus, whilst there is good evidence for the benefits of testosterone replacement in men with a total testosterone !7 nmol/l (200 ng/dl), the role of androgen replacement in milder degrees of androgen deficiency is less clear.…”
Section: Who To Treatmentioning
confidence: 71%